Narrowband UVB phototherapy in pityriasis rosea - Vijayeeta Jairath; Madan Mohan; Nidhi Jindal; Paritosh Gogna; Clarify Syrty; Priyadarshini Mookalamada Monnappa; Sarabjit Kaur; Manu Sehrawat (Indian Dermatology Online Journal, 2015)
Objective: Pityriasis rosea (PR) is an acute self-limiting disease. Despite vigorous efforts by generations of researchers since nearly 150 years, present treatment modalities for PR are not very gratifying. Ultraviolet radiation has been recommended in PR, although only a few studies validate this proposal. This study was conducted to explore the therapeutic effect of NBUVB on the symptoms, course, and severity of PR. Materials and Methods: This study involved a hundred patients who were randomly divided into two groups, using computer-generated randomization chart. Group A underwent treatment with fixed dose NBUVB of 250 mJ/cm2 three times (nonconsecutive) a week for 4 weeks. Group B formed the placebo group who did not receive any treatment. The two groups were compared with each other for the intensity of pruritis, course and duration of disease, and PR severity score (PRSS). Results: The t values of improvement in PRSS score in Group A (t = 12.796) were higher as compared with that in Group B (t = 10.066). Similarly, the t value of the pruritus scale in Group A (t = 7.758) was higher than Group B (t = 5.754) indicating the symptomatic improvement in itching. Conclusion: Fixed-dose NBUVB phototherapy resulted in marked improvement in the severity and symptoms of the disease as quantitatively assessed by PRSS.